2021
DOI: 10.3389/fpsyt.2021.669042
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Smartphone Use Is Associated With Health Problems in Adolescents and Young Adults

Abstract: Background and Aims: This present paper will review the existing evidence on the effects of excessive smartphone use on physical and mental health.Results: Comorbidity with depression, anxiety, OCD, ADHD and alcohol use disorder. Excessive smartphone use is associated with difficulties in cognitive-emotion regulation, impulsivity, impaired cognitive function, addiction to social networking, shyness and low self-esteem. Medical problems include sleep problems, reduced physical fitness, unhealthy eating habits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 98 publications
(85 reference statements)
5
97
0
3
Order By: Relevance
“…Smartphone addiction has been associated in some studies with increased depression among adolescents, including among those in low-income families [5,6,[21][22][23]. Since COVID-19, middle and high school students have been less likely to meet their friends in person due to the risk of spreading coronavirus.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphone addiction has been associated in some studies with increased depression among adolescents, including among those in low-income families [5,6,[21][22][23]. Since COVID-19, middle and high school students have been less likely to meet their friends in person due to the risk of spreading coronavirus.…”
Section: The Current Studymentioning
confidence: 99%
“…Compared to before the pandemic, children and adolescents have drastically increased their screentime, including their use of smartphones, and more children and adolescents are considered to be addicted to their smartphone or are engaging in problematic smartphone use than before the pandemic [1,2]. Moreover, children and adolescents are more depressed now than before the pandemic [3,4], and smartphone addiction and problematic smartphone use have been found to be positively associated with depression, although this data includes studies conducted before COVID-19 [5,6]. Researchers have also found that socioeconomic status may be associated with depression among children and adolescents, including during the COVID-19 pandemic [7,8], but other potential factors influencing smartphone addiction and depression, such as whether they have siblings to socialize with during periods of home confinement, have been understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the three-dimensional, 18-item Gaming Hazard Assessment Scale not only included the diagnostic criteria of DSM-5, but also accounted for the clinical characteristics and game behavior patterns of ICD-11's GD diagnostic criteria, which improves the efficacy of large-scale risk screening tests for GD. Subsequent studies should consider combining the Gaming Hazard Assessment Scale with other approaches (e.g., long-term dynamic assessments of social and cognitive function, somatization disorder, and quality of life assessments), to better inform prognosis and treatment plans ( 42 44 ). Isolated studies that create multiple tools, produce an incoherent and unconvincing evidence base, so there is a need to provide a more robust theoretical and methodological basis for GD or other behavioral addictions in the population (e.g., a more integrated screening, diagnosis, and assessment system) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dies ist deswegen von großer Bedeutung, weil man diese Ergebnisse in einen größeren Rahmen stellen kann, der dann ihre Bedeutung verdeutlicht. [21]. Die Autoren enden mit einer klaren Schlussfolgerung: "Exzessive Smartphone-Nutzung ist mit psychiatrischen, kognitiven, emotionalen, medizinischen und Gehirnveränderungen verbunden, die von Gesundheits-und Bildungsexperten berücksichtigt werden sollten."…”
Section: Viel Zeit Mit Youtube Arme Kinderunclassified